Mengatasi Kesulitan dalam Berbahasa Inggris - I Nyoman Muliana (Warmadewa Press, 2020)
Learning English is still quite difficult, especially among junior high school students. Learning difficulties due to the lack of motivation to learn, infrastructure, learning materials and environment. The difficulty often faced by students is about pronunciation or speaking ability. The atmosphere of the Covid-19 pandemic is a major problem in the implementation of teaching because learning is carried out online and this is a new challenge for students and educators, therefore to increase learning interest for students, learning is still designed as well as possible so that students are able to participate in learning. Based on the phenomenon, the Master of linguistics at Warmadewa University takes part through community service activities by holding training programs in the form of online learning about how to speak English so that students have high motivation even in a pandemic situation. This is done with the aim of assisting students in improving their English language skills of Swastika students located in Badung District which is not far from the Warmadewa University. The four language skills that help students learn a language are writing, reading, listening and speaking. This study was designed using qualitative research with the FGD method. This study aims to explain the difficulty of English among junior high school level students.